Understanding Language Interference in Multilingual Contexts for Inclusive English Language Education - Mukmin25; Wahyu Erinyanti, Ribut; Arista Asih, Ria (International Journal of English Language and Pedagogy, 2025)
Language interference refers to deviations from the rules of the target language due to the influence of a speaker’s first or second language. This study aims to identify and analyze the forms of English language interference experienced by multilingual students, providing an empirical foundation for developing inclusive and linguistically responsive English language education that accommodates learners’ diverse linguistic backgrounds. Employing a qualitative case study design, the research focuses on students from the English Language Education Program at the University of Muhammadiyah Luwuk, who use multiple languages in their daily lives. Data collection instrument was interview. The findings reveal two primary forms of interference in students’ English communication: phonological and syntactic interference. Phonological interference stems from sound similarities students’ source language and English, while syntactic interference arises from the influence of first and second language syntax on English sentence construction. These findings underscore the importance of understanding learners’ linguistic backgrounds as a basis for fostering more inclusive English language teaching practices in multilingual classrooms.